2020
DOI: 10.1002/dmrr.3408
|View full text |Cite
|
Sign up to set email alerts
|

Features and long‐term outcomes of patients hospitalized for diabetic ketoacidosis

Abstract: Background Diabetic ketoacidosis (DKA) is an acute metabolic complication characterized by hyperglycaemia, ketones in blood or urine, and acidosis. Objective The aim of this study was to characterize features of patients hospitalized for DKA, to identify triggers for DKA and to evaluate the long‐term effects of DKA on glycaemic control, complications of diabetes, re‐hospitalizations, and mortality. Methods Historical prospectively collected data of patients hospitalized to medical wards for DKA between 2011 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The clinical manifestations of DKA include dehydration, Kussmaul respiration, nausea, vomiting, abdominal pain, loss of consciousness, leukocytosis, and increased serum amylase [4].A study showed that mortality rate was 9 %, and readmission for DKA rate was 31 % during over 7 years of follow-up of patients with DKA [15]. DKA mainly occurs in patients with type 1 diabetes mellitus, but it can also occur in patients with type 2 diabetes mellitus [16].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of DKA include dehydration, Kussmaul respiration, nausea, vomiting, abdominal pain, loss of consciousness, leukocytosis, and increased serum amylase [4].A study showed that mortality rate was 9 %, and readmission for DKA rate was 31 % during over 7 years of follow-up of patients with DKA [15]. DKA mainly occurs in patients with type 1 diabetes mellitus, but it can also occur in patients with type 2 diabetes mellitus [16].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors Between 6% and 21% of adults present with DKA as their initial diagnosis of type 1 diabetes [21,24,44]. In adults with a known history of diabetes, the most common precipitating factors for DKA include infections, intercurrent illnesses, psychological stress, and omission or insufficient use of insulin therapy, as described in Table 1 [24,27,28,30,38,[44][45][46][47][48][49][50][51][52]. Worldwide, infection is the most common precipitating factor for DKA, occurring in 14-58% of cases [3,24].…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…However, patients with type 2 diabetes were excluded from this study. 12 The major diagnostic challenge in adult patients with new-onset diabetes presenting with ketoacidosis or ketosis is to elucidate whether it is caused by type 1 or ketosis-prone type 2 diabetes. It is essential to increase awareness and facilitate an understanding of ketosis-prone type 2 diabetes among clinicians, as it is still a new entity with an incompletely characterised prevalence and clinical course.…”
Section: Introductionmentioning
confidence: 99%
“…A recent publication showed that one fifth of adult patients admitted for DKA were newly diagnosed with diabetes. However, patients with type 2 diabetes were excluded from this study 12 . The major diagnostic challenge in adult patients with new‐onset diabetes presenting with ketoacidosis or ketosis is to elucidate whether it is caused by type 1 or ketosis‐prone type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%